2020
DOI: 10.1136/bmjopen-2020-037567
|View full text |Cite
|
Sign up to set email alerts
|

Physician staffed emergency medical service for children: a retrospective population-based registry cohort study in Odense region, Southern Denmark

Abstract: ObjectivesThe aim of this study is to determine diagnostic patterns in the prehospital paediatric population, age distribution, the level of monitoring and the treatment initiated in the prehospital paediatric case. Hypothesis was that advanced prehospital interventions are rare in the paediatric patient population.SettingWe performed a retrospective population-based registry cohort study of children attended by a physician-staffed emergency medical service (EMS) unit (P-EMS), in the Odense area of Denmark dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The differences in the distributions of age and sex in the two groups might be due to the greater incidence of trauma among male adolescents than females and the more frequent suicide attempts among adolescents than younger children. Several previous studies have reported similar trends (18,19). There was a higher proportion of children younger than four years in the non-EMS group, which might be associated with their light body weight and mild symptoms caused by respiratory infection.…”
Section: Clinical Characteristics Of the Ems Group Distinct From Thos...supporting
confidence: 66%
“…The differences in the distributions of age and sex in the two groups might be due to the greater incidence of trauma among male adolescents than females and the more frequent suicide attempts among adolescents than younger children. Several previous studies have reported similar trends (18,19). There was a higher proportion of children younger than four years in the non-EMS group, which might be associated with their light body weight and mild symptoms caused by respiratory infection.…”
Section: Clinical Characteristics Of the Ems Group Distinct From Thos...supporting
confidence: 66%
“…The rates of nontransport of patients after contact with ambulances staffed by EMTs and paramedics vary from 3.7% to 93.7% in very selected cases. 22 , 23 , 24 In another Danish study from a different health region, 22 consultations between EMTs or paramedics and a physician at the emergency medical dispatch center resulted in the release of more patients with noncritical presentation at the scene with high patient satisfaction and without compromising patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…The national Emergency Medical Service (EMS) system is divided into five health care regions, using the same national prehospital electronic patient records [ 40 ]. In cases of suspected POHCA, an ambulance and an anesthesiologist-paramedic staffed mobile critical care unit are dispatched [ 41 ]. Most areas are accessible with response times below 20 min [ 39 ].…”
Section: Methodsmentioning
confidence: 99%